Perancangan Gym Center Dengan Fasilitas Penunjang Bagi Pengguna di Surabaya - Liam, Wil (Intra, 2017)
Surabaya is a city with a lot of active population ranging from children, adolescents, to adults. Of course the daily activities are so busy that it is almost impossible to spend time because of the busyness of each. Side effects are obtained when continuous life pattern like that is susceptible to disease, bone loss, and stiff muscles. For that it is necessary a facility that can support so that all the bad impact can be prevented. Thus emerges an idea and design that can accommodate all that. In the design of this gym there are enough facilities to meet the needs of the sport.